The Use of Padlet to Improve Japanese Learners' Collaborative Learning on Basic Composition Writing Skills (Sakubun) - Noviyanti Aneros; Herniwati Herniwati (JAPANEDU: Jurnal Pendidikan dan Pengajaran Bahasa Jepang, 2023)
The integration between the Industrial Revolution 4.0 and the education sector requires teachers and students to utilize nowadays technologies, one of them using Padlet. Padlet is a web-based application that enables users to write or pin-up files such as pictures on its’ virtual walls. This study aims the utilization of Padlet to enhance students' Japanese composition skills in a Japanese basic writing class (Shokyu Sakubun). Involving a class of 15 (fifteen) students enrolled in a basic writing course at a state university in Bandung, West Java, this study attained the data through pre-test, post-test, and students' essay observations during four times treatments and questionnaires. The findings showed that there is a significant increase in the average grades after using Padlet for collaborative learning in basic Japanese writing courses, which is seen from the results of the pre-test and post-test. It can be interpreted that Padlet was helpful for Japanese learners to improve their competence in Japanese writing skills. The findings also showed that the respondents gave positive responses to Padlet utilization. Further, Padlet can be used not only as a medium in teaching but also as a medium to store and distribute teaching materials from teachers to students or vice versa, hence it is useful as an application to enhance Japanese language learning in general.